2018
DOI: 10.1111/trf.14613
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐free nucleic acids are present in blood products and regulate genes of innate immune response

Abstract: CFNAs are present in blood products. Immunoregulatory properties of CFNA are shown in vitro, providing new insights on biologically active components of blood products besides those for intended therapeutic use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
(68 reference statements)
0
18
0
Order By: Relevance
“…It has been demonstrated that the cell-free DNA content in red cell concentrates assessed by the Quant-iT PicoGreen assay is exceedingly low at around 1 ng/mL, (1) and via a different methodology, it has been shown that the DNA content of platelet concentrates and FFP is lower than that of red cell concentrates. (2) Furthermore, it has been established that preanalytical sampling errors, which are common in the clinical setting, may lead to spuriously high cell-free DNA levels, and these falsely elevated cell-free DNA levels would not be captured by a technically superior detection method. (3) In addition, we would like to emphasize that regardless of the origin of the cell-free DNA, elevated levels were associated with activation of coagulation, making it an interesting target for therapeutic strategies.…”
Section: To the Editormentioning
confidence: 99%
“…It has been demonstrated that the cell-free DNA content in red cell concentrates assessed by the Quant-iT PicoGreen assay is exceedingly low at around 1 ng/mL, (1) and via a different methodology, it has been shown that the DNA content of platelet concentrates and FFP is lower than that of red cell concentrates. (2) Furthermore, it has been established that preanalytical sampling errors, which are common in the clinical setting, may lead to spuriously high cell-free DNA levels, and these falsely elevated cell-free DNA levels would not be captured by a technically superior detection method. (3) In addition, we would like to emphasize that regardless of the origin of the cell-free DNA, elevated levels were associated with activation of coagulation, making it an interesting target for therapeutic strategies.…”
Section: To the Editormentioning
confidence: 99%
“…ecDNA comprises mainly nuclear DNA (nucDNA) and mitchondrial DNA (mitDNA). It is also present in the extracellular milieu of blood products (as shown in Table 1) [11][12][13][14][15][16][17][18][19][20]. However, a novel and significant role of ecDNA has emerged, involving its ability to trigger innate immune system responses and drive inflammation when released from mechanically injured cells [21].…”
Section: Introductionmentioning
confidence: 99%
“…In the case of blood products, the following criteria must be carefully considered when choosing the extraction method: (i) due to a leukocyte reduction prior to manufacturing, total nucleic acids are present at very low concentrations. As a case in point, we observed in FFP a dsDNA concentration ranging from 2.8 ± 0.9 ng/mL [27]; (ii) RBCU contain mainly conservation buffer and erythrocytes (hemoglobin); (iii) PC mainly contain residual plasma, conservation buffer and platelets. From our experience, methods designed for the isolation of cell-free nucleic acid from all three types of blood products showed good yields [27].…”
Section: Technical Aspects Of Ngs Applied To Blood Products and Donormentioning
confidence: 99%
“…As a case in point, we observed in FFP a dsDNA concentration ranging from 2.8 ± 0.9 ng/mL [27]; (ii) RBCU contain mainly conservation buffer and erythrocytes (hemoglobin); (iii) PC mainly contain residual plasma, conservation buffer and platelets. From our experience, methods designed for the isolation of cell-free nucleic acid from all three types of blood products showed good yields [27]. …”
Section: Technical Aspects Of Ngs Applied To Blood Products and Donormentioning
confidence: 99%
See 1 more Smart Citation